Socialization Material for Sheep Breed Health Management - Rifky Ramdhani; Budi Susanto; Bayu arisandi; Supriyono (Ann Publisher, 2024)
Raising sheep is a livelihood known since the time of the Prophet Adam. Sheep raising was a childhood and adolescent profession of prophets before being appointed prophets and Rosul. Sheep farming developed from grazing until it was domesticated. Sheep farming activities include the selection of suitable breeds, the construction of clean pens, nutritious feeding following the nutritional needs of the sheep raised, and health management to keep sheep healthy. Sheep health management has been socialized at CV Saudagar Group, Cianjur Regency, West Java Province. The socialization conveyed that sheep health management includes maintaining health through preventive and curative actions. Preventive measures include feeding according to needs, giving vitamins, building clean cages, and environmental management. Curative action in the form of treatment if the sheep is already sick with chemical and herbal medicines.